Effect of the ceramic translucency on the long-term water sorption and solubility of resin cements - Ana Paula Menezes Vaz Queiroz; Mariana Menezes Vaz Queiroz; Saryta Argolo; Richard Mark Foxton; Paula Mathias; Andrea Nóbrega Cavalcanti (Universidade Estadual de Campinas, 2020)
Aim: The aim of this study was to evaluate the influence of the translucency of ceramic on water sorption and solubility of resin cements over time. Methods: Lithium disilicate ceramic slides (15x15x1 mm), A1 in color and with different translucencies (high-medium-low) were manufactured; and a glass slide with similar dimension was used as control. Under every slide, 15 specimens (8x0.5 mm) from each resin cement were prepared: light-cured (RelyX Veneer); conventional dual-cured (RelyX ARC); and self-adhesive dual-cured (Rely-X U200). The specimens were then sub-divided according to the period of evaluation (immediately, after 6 and 12 months of storage) (n=5). To evaluate the loss or gain of mass, the specimens were dried until a constant mass was reached. Subsequently, they were divided according to the respective period of storage at 37°C in distilled water and weighed immediately following removal from water. After each period, specimens underwent a new dehydration. Values from water sorption and solubility were calculated and statistically analyzed (Anova 3-way/Tukey test). Results: The lower translucency resulted in greater water sorption and solubility for all cements, regardless of the experimental period. The self-adhesive dual-cured cement showed higher water sorption under all experimental periods and had worse values after 1 year aging. Differences among solubility could only be detected after aging, and the light-cured material had higher values after 6 and 12 months. Conclusions: It could be concluded that the low degree of translucency can negatively influence the passage of light and interfere on the durability of the resin cement. The conventional dual-cured resinous agent seemed to be less affected by such condition.